A resuscitation room guide - Banerjee, Ashis; Hargreaves, Chris (Oxford : Oxford University Press, 2007)
Designed to be a portable, accessible, and practical guide to the various conditions that present in the resuscitation room this title covers their recognition, assessment and management and the equipment and investigative procedures used.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Resuscitation; Hospitals -- Emergency services